Social Wellbeing and the Values of Small-scale Fisheries (MARE Publication Series,, 2018)
This book advances discussions of values in fisheries by showing the rich theoretical insights and connections possible when value is grounded in a multi-dimensional social well being approach. Questions of value have long been a central, if often unacknowledged, concern in maritime studies and in research on fisheries. Social scientists have looked at changing perceptions of value as coastal regions and fisheries have industrialized, economic interconnections have deepened, ecosystems have been depleted, shifts in population have occurred, and governance arrangements have been transformed. With a focus on the diverse ways in which small-scale fisheries are valued, the contributions to this volume address these and other themes through cases from numerous countries in Asia, Europe, and Latin America. "This volume provides a timely contribution to the development of new approaches that seek to capture the complexity of how fisheries can be understood beyond standard mo no-dimensional, and often economic, interpretations. Each chapter makes a clear and stand-alone contribution to conceptual and methodological advancement, and collectively these works cover a wide range of frameworks and schools of thought." Dr Sarah Coulthard, Senior Lecturer in International Development, Northumbria University, UK "The list of contributing authors [is] impressive and covers a wide geographical range of illustrative examples, [which] helps to demonstrate the global value of small-scale fisheries." Professor J. Allister McGregor, Professor in Political Economy, the University of Sheffield, UK.